Women in Command: The Matildine War of 1141. (11th October 2022) - Isaac, Steven
Abstract : In 1141, Queen Matilda III of England and the Empress Matilda were active military commanders in the field against one another, often facing the same risks as their armies. Besides being worthy of attention as one of the rare moments when two women campaigned directly against each another, the conflict also has the advantage of having left enough documents from the women themselves to allow their voices to be heard alongside the gendered narrative of medieval chroniclers. What emerges here is a campaign history that confirms how both medieval men and women accepted the generalship of women, that shows how each woman was prepared by prior experience to manage complex administrations, and how, in the crisis moments of war, they navigated the pressures of medieval warfare.